2023
DOI: 10.1088/1748-605x/ad0d84
|View full text |Cite
|
Sign up to set email alerts
|

A leptin-loaded poly-ϵ-caprolactone 3D printing scaffold for odontoblastic differentiation in human dental pulp cells

Eun-Hyo Cho,
Ye-Seul Kim,
Young-Ran Kim
et al.

Abstract: This study investigated the effects on odontoblast differentiation of a 3D-printed poly-ε-caprolactone (PCL) scaffold that incorporated leptin. Material extrusion-type 3D printing with a 43,000-molecular weight PCL material was used to fabricate a PCL scaffold with a 6 mm diameter, 1 mm height, and 270 to 340 µm pore size. The experimental groups were PCL scaffolds (control group), PCL scaffolds with aminated surfaces (group A), and PCL scaffolds with leptin on the aminated surface (group L). The aminated surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Therefore, in this study, bone regeneration was promoted by coating the scaffold with leptin and osteolectin, which are growth factors that stimulate osteogenic differentiation [38][39][40][41][42][43][44]. Adhesion and distribution of leptin and osteolectin were performed as previously described [51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in this study, bone regeneration was promoted by coating the scaffold with leptin and osteolectin, which are growth factors that stimulate osteogenic differentiation [38][39][40][41][42][43][44]. Adhesion and distribution of leptin and osteolectin were performed as previously described [51].…”
Section: Discussionmentioning
confidence: 99%
“…It is mainly produced in adipose tissue and acts on the hypothalamus of the brain to regulate appetite and metabolism. The main function of leptin is related to the regulation of energy homeostasis, but it also has various effects on other physiological processes, including bone metabolism [38][39][40][41]51]. Leptin receptors are present in osteoblasts, the cells responsible for bone formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of measurement with a stereoscopic microscope, the pore size of the PCL scaffolds was 270-340 µm [30]. A previous study using SEM reported that untreated PCL specimens have smooth surfaces, whereas crystalline deposits were confirmed on the surface of both aminated PCL scaffolds and aminated PCL scaffolds treated with Arg-Gly-Asp (RGD) [32].…”
Section: Surface Morphologymentioning
confidence: 95%
“…PCL (Mn = 43 000 g mol −1 ; Polysciences, USA) was put into a syringe attached to a Dr INVIVO 4D6 (Rokit Healthcare, Seoul, Korea) printer and melted at 75 • C. The PCL was sprayed with a 0.4 mm diameter nozzle to prepare a lattice-shaped specimen with a pore density of 65%, diameter of 30 mm, and height of 1 mm [29]. The pore size of the PCL specimen was measured using a stereomicroscope (EGVM-452M, EG Tech, Ansan, Korea) [30]. Then, PCL scaffolds were made into disks with a 6 mm diameter using a puncher.…”
Section: Preparation Of Pcl Scaffoldsmentioning
confidence: 99%